Les collections de plâtres des églises et châteaux. L’exemple bourguignon - Michaël Vottero (In Situ)
The plaster casts made during the restoration of religious buildings during the nineteenth century were often neglected, but are today gradually becoming better understood and exhibited. Alongside the traditional workshop plasters used as models by stonemasons, like the trumeau of the gateway at the Autun cathedral, by Pascal, the practice of taking moulds initiated by Viollet-le-Duc was pursued throughout the nineteenth century. This practice of making a plaster cast of an architectural ornament that was removed from its initial place, in order to restore it or to make a copy of it, was first developed during the works carried out on the Vézelay basilica. The recent discovery of the plasters made of the synodal palace at Sens, also associated with Viollet-le-Duc, is further evidence of this practice. With these examples from the Burgundy region, we shall examine anew the use of plaster casts in the major restoration operations during the nineteenth century.